The Influence of Digital Literacy on Motivation and Learning Achievement in Fiqh Among Students of MA Badrul Islam Gulung - Jayadi, Arman; Firmansyah, Didi; Yusuf Arfizi, Muhammad; Amir Ali, Muhammad; Supardi, Supardi (AS-SABIQUN, 2025)
The purpose of this study was to investigate how digital literacy influences students' motivation and Fiqh academic achievement at MA Badrul Islam Gulung. A quantitative descriptive correlational approach was employed, with a sample of 23 purposively selected twelfth-grade students. Data were collected using questionnaires to assess digital literacy and motivation, semester exam scores for academic achievement, and observations on the use of technology in learning. The data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results revealed a significant positive correlation between digital literacy and both learning motivation (r = 0.652, p < 0.05) and academic achievement in Fiqh (r = 0.718, p < 0.05). Digital literacy accounted for 42.5% of the variance in learning motivation and 51.5% of the variance in academic achievement. These findings suggest that students with higher levels of digital literacy are more motivated and perform better academically, particularly in Fiqh. The study concludes that digital literacy plays a critical role in enhancing students' motivation and academic success. It emphasizes the need for integrating digital literacy into the educational curriculum, particularly in Islamic education, to foster better learning outcomes and equip students with the necessary skills for success in a technology-driven world. This highlights the importance of digital literacy as an essential component of modern educational practices.